Finding of Arachnoidea (Arachnoidella) protecta harmer, 1915 (bryozoa ctenostomatida, arachnidiidae) in the mediterranean sea - Gusso, C. C.; D'hondt, J.; Nicoletti, L.; Cuscani, G. G. (Italian Journal of Zoology, 1998)
A species of Arachnoidea unknown in the Mediterranean Sea was collected during a survey on the benthos at Vulcano Island (Sicily), and was identified as A. (Arachnoidella) protecta, described by Harmer (1915) from the coastal waters of Celebes Island (Western Pacific Ocean).